A society for international development : prospectus 1984 - Mattis, Ann.; Society for International Development (Durham, N.C. : Published by Duke University Press in collaboration with the Society for International Development, 1983)
This book is intended to carry the progressives' debate and search for solutions to a wider audience as a matter of utmost urgency.
Selected proceedings from the 25th anniversary world conference of the Society for International Development held in July 1982 in Baltimore, Md.
"A special double issue of Development, seeds of change, village through global order, 1983:3 and 4"--P. [ii]
Includes bibliographical references and index.
hza 28/01/2019
Loans
Keywords: Economic development